Drought Disaster Analysis Using the Standardized Precipitation Index (SPI) Under the Influence of ENSO and the IOD in the Northern Region of Banten Province (1991–2020 Period) - Dodi Saputra; Pakhrur Razi (EarthCare, 2026)
Drought is a physical phenomenon that begins with reduced rainfall (meteorological drought) and can develop into agricultural and hydrological drought through heat and water-vapor transfer processes driven by sea surface temperature anomalies such as El Niño and the Positive Dipole Mode (IOD), which suppress cloud formation and rainfall over Indonesia. This study in the northern region of Banten Province (Serang and Tangerang) for the 1991–2020 period analyzes meteorological drought using the Standardized Precipitation Index (SPI) and relates it to ENSO (ONI) and the IOD. The results show that the most severe extreme drought occurred during the three-month deficit period of October–December 1997 with an SPI of −3.9 and during the six-month deficit period of January–June 2003 with an SPI of −4.1, while the most spatially widespread drought pattern across northern Banten occurred during the three-month SPI period. A strong El Niño event (ONI > +2) and a positive IOD phase (IOD > +1) in 1997 were associated with reduced atmospheric moisture and decreased rainfall, triggering extreme drought that appeared widespread in the three-month SPI map.